2020
DOI: 10.1038/s41598-020-72009-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating altered brain development in infants with congenital heart disease using tensor-based morphometry

Abstract: Magnetic resonance (MR) imaging studies have demonstrated reduced global and regional brain volumes in infants with congenital heart disease (CHD). This study aimed to provide a more detailed evaluation of altered structural brain development in newborn infants with CHD compared to healthy controls using tensor-based morphometry (TBM). We compared brain development in 64 infants with CHD to 192 age- and sex-matched healthy controls. T2-weighted MR images obtained prior to surgery were analysed to compare voxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 96 publications
5
21
3
1
Order By: Relevance
“…Consistent with previous studies, 11 , 15 including in this cohort, 12 we observed that infants with CHD had reduced brain tissue volumes and increased extracerebral CSF before surgery. However, to our knowledge, this is the first use of a normative modelling approach to assess brain development in individual infants with CHD.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, 11 , 15 including in this cohort, 12 we observed that infants with CHD had reduced brain tissue volumes and increased extracerebral CSF before surgery. However, to our knowledge, this is the first use of a normative modelling approach to assess brain development in individual infants with CHD.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to these findings, in a heterogenous sample of CHD infants, significant positive correlations were observed between CDO 2 and whole brain, cortical grey matter and deep grey matter volumes (26,27,31) along with cortical gyrification (26) and cortical microstructural development (27) . However, using tensor-based morphometry, after accounting for global brain size, no significant associations between CDO 2 and structural brain development at a voxel-wise level were identified (31). We suggest this reflects that either reduced CDO 2 impairs growth across the whole brain with no specific regional vulnerability to low CDO 2 in the neonatal period, or that there was insufficient statistical power in our study to determine voxel-wise differences related to CDO 2 after correcting for the many multiple comparisons undertaken in voxel-wise analyses.…”
Section: The Relationship Between Haemodynamic Factors and Brain Development In The Neonatal Periodsupporting
confidence: 78%
“…CDO 2 was significantly reduced in SVP and TGA infants compared to controls, pre-operative brain volume was significantly lower in the CHD sample and there was a significant positive association between CDO 2 and brain volumes (25). Similar to these findings, in a heterogenous sample of CHD infants, significant positive correlations were observed between CDO 2 and whole brain, cortical grey matter and deep grey matter volumes (26,27,31) along with cortical gyrification (26) and cortical microstructural development (27) . However, using tensor-based morphometry, after accounting for global brain size, no significant associations between CDO 2 and structural brain development at a voxel-wise level were identified (31).…”
Section: The Relationship Between Haemodynamic Factors and Brain Development In The Neonatal Periodsupporting
confidence: 62%
“…including the CC, in fetuses with CHD before 32 weeks' gestation 24 . Reduced brain volumes in infants with CHD have also been described to persist postnatally in neonates prior to surgery 16,25 and in teenagers 36 , with a significant reduction in the isthmus 16 and the splenium 16,25 of the CC. Experimental data have shown that chronic exposure of the developing brain to low oxygen concentrations resulted in a smaller CC in rats 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The CC is a well‐defined brain structure that can be measured reliably in the midsagittal plane using transvaginal neurosonography (NSG) 23 . Recent studies have shown significant reduction in CC volume in CHD fetuses 24 and neonates before surgery 16,25 . Likewise, CC size during the fetal period has been shown to be affected in high‐risk conditions such as intrauterine growth restriction (IUGR) and preterm birth 19,26,27 .…”
Section: Introductionmentioning
confidence: 99%